2020
DOI: 10.29121/granthaalayah.v5.i12.2017.470
|View full text |Cite
|
Sign up to set email alerts
|

Practices and Challenges of Public and Private Preschools of Jigjiga City Administration

Abstract: The main purpose of this study was to assess practices and challenges of preschool education in Jijiga City administration. Mixed design was employed (both quantitative and qualitative) for this study. 19 preschool centres (6 public and 13 private preschools) were randomly selected for the study. 51 preschool teachers (12 teachers from public and 39 teachers from private teacher) were selected.  A semi-structured questionnaire was used to collect quantitative data in which 57 items were filled by presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Teachers’ training plays a significant role in education in updating and giving new information to the trainees and filling the gaps that the trainees have. However, studies conducted in Ethiopia indicate that most preschool teachers are untrained or have minimal training (Assefa, 2014; Mulugeta, 2015; Tirussew et al, 2009) and staff have irrelevant or only slightly relevant qualifications (Astatke and Kassaw, 2017; Fantahun, 2016; Haile and Mohammed, 2017; Rahel, 2014; Tigistu, 2013). Even the caregivers in private kindergarten schools in urban areas provide services without having pre-service or in-service training (Astatke and Kassaw, 2017).…”
Section: Challenges That Hinder the Provision Of Quality Ecce In Ethiopiamentioning
confidence: 99%
See 4 more Smart Citations
“…Teachers’ training plays a significant role in education in updating and giving new information to the trainees and filling the gaps that the trainees have. However, studies conducted in Ethiopia indicate that most preschool teachers are untrained or have minimal training (Assefa, 2014; Mulugeta, 2015; Tirussew et al, 2009) and staff have irrelevant or only slightly relevant qualifications (Astatke and Kassaw, 2017; Fantahun, 2016; Haile and Mohammed, 2017; Rahel, 2014; Tigistu, 2013). Even the caregivers in private kindergarten schools in urban areas provide services without having pre-service or in-service training (Astatke and Kassaw, 2017).…”
Section: Challenges That Hinder the Provision Of Quality Ecce In Ethiopiamentioning
confidence: 99%
“…Haile and Mohammed (2017) found that there is a lack of accessible training institutions. Furthermore, the training given is too theoretical and insufficient to support practitioners to acquire the required professional skills for the real work setting.…”
Section: Challenges That Hinder the Provision Of Quality Ecce In Ethiopiamentioning
confidence: 99%
See 3 more Smart Citations